Wpływ promieniowania gazu oraz sublimacji ścianki na parametry przepływu gazu za odbitą silną falą uderzeniową - KOPYSTYŃSKI, Jacek (Engineering Transactions, 1970)
Influence of the radiation of gas and sublimation of the wall on the parameters of gas flow behind a strong reflected shock waveA model is considered of the phenomenon of the reflection of a shock-wave from a sublimating wall. The sublimation occurs under the influence of the radiation flux emitted from a hot gas. It is assumed that the only effects perturbing the gas flow behind the reflected wave are radiation energy losses and the action of the gas «piston» arising from the sublimation and separated from the gas by a surrounding stationary (not subjected to diffusion) surface of separation. With the assumed formula for radiation transport and known velocity of sublimation the linearized equations or gasodynamics was solved, obtaining an analytical expressions for the corrections of the parameters of the state of gas and velocity of the reflected wave, dependent on the radiation and sublimation. The relative influence of both these factors on the found correction is discussed.In conclusion, the range of applicability is discussed of the model used in this paper.